Improving Reflectors Visualization by Implementing Surface-Consistent Deconvolution in 2D Seismic Data Related to the Western Region of Iraq - Khalaf, Zeyad H.; Al-Rahim, Ali M. (Iraqi Journal of Science, 2026)
This study concentrates on the analysis of 2D seismic reflection surveying data obtained from a seismic line characterized by a considerable amount of noise and reverberations. The goal is to enhance data quality by employing the surface-consistent deconvolution technique, which encompasses two variations; gapped and spike deconvolution. The unique applications offered by utilizing the Global Claritas software to achieve optimal outcomes, which assist in the quality of seismic data analysis and interpretation. Several tests were carried out on the seismic data, revealing that the application of Spike deconvolution with an operator length of 220 milliseconds and a prediction lag of 2 milliseconds led to enhancements in the data. This process improved the wavelet continuity and reduced noise levels. Through the tests conducted on gapped deconvolution, it was determined that the optimal operator length for the data is 220 milliseconds, accompanied by a prediction delay of 20 milliseconds, which got excellent results in eliminating reverberations and improving the vertical resolution of the seismic. The deconvolution application technique was effective in reducing noise for shallow-depth data. According to the results extracted after applying Gapped deconvolution, it is regarded as the most effective method for the data pertaining to the western region, as well as offering a clearer image of the subsurface reflectors, this would increase the resolution of the seismic section in detecting reflection surfaces and to distinguish seismic attributes.